Pilus genes in Escherichia coli isolated from pigs with diarrhea - Nietfeld, Jerome C.; Yeary, T. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A retrospective survey of the Kansas State Veterinary Diagnostic Laboratory records was made for Escherichia coli isolated from pigs with diarrhea. There were 111 E. coli isolates that carried genes for attachment pili that are necessary for E. coli to cause diarrhea. Of the 111 isolates, 103 had one pilus gene and eight had two pilus genes. The most common pilus type was the K88 pilus accounting for 73% of the isolates. All but one of the K88 isolates also carried at least one toxin gene indicating that they were virulent for pigs. The next most common pilus type was F18 accounting for 21% of the isolates. However, more than half of the F18 isolates did not have detectable toxin genes. F41, K99, and 987P pilus types made up 7%, 4%, and 2% of the isolates, respectively (percentages total greater than 100% because some isolates had 2 pilus genes). Escherichia coli expressing pilus types K88 and F41 are currently the major causes of colibacillosis in pigs.
Keywords: Swine; Escherichia coli; Pilus gene